RETRACTED: Influence of Work Environment, Work Motivation and Work Experience on Employee Performance PT. Pranaja Trimitra Indonesia - Kayla Diatry Ramadhani; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
Study This aim For know influence Environment Work, Work Motivation, and Work Experience on performance his employees. Technique This research utilizes a quantitative approach, with survey methods chosen as the primary data source. Primary data used for research This shaped questionnaire Which given to 67 person employee PT. Pranaja Trimitra Indonesia. Technique analysis data in study This covers regression linear multiple And hypothesis test (test t) Which processed using SPSS 23 application. From results study can seen that experience Work produce positive influence on employee performance, while the work environment and motivation Work No produce positive effect to performance employee.